EMPATI DAN INTEGRITAS: MEMBANGUN KARAKTER DI ERA DIGITAL DI DESA BOTOHILI SILAMBO - Novita Satria Gulo (Haga : Jurnal Pengabdian Kepada Masyarakat, 2023)
The community service program "Empathy and Integrity: Building Character in the Digital Era" was implemented in Botohili Silambo Village to address the social challenges arising from technological advancements. With a focus on character education, this program aims to enhance awareness and application of the values of empathy and integrity among the youth. Through interactive methods such as workshops, group discussions, and collaborative projects, participants are invited to understand and internalize these values. Evaluation results show a significant increase in participants' understanding of the importance of empathy and integrity in daily interactions. Additionally, there has been a positive change in behavior, including increased participation in social activities and more responsible use of digital media. This program is expected to contribute to the formation of a more harmonious and integrity-driven society, and serve as a model for similar initiatives in the future.